Online Education Among Senior Secondary Students of Rural Area of Varanasi District: Prevalence and Challenges - Mishra, Pooja; Kumari, Pushpa (Indian Journal of Extension Education, 2024)
During COVID-19 pandemic lockdown, online education emerged as an essential component of the education system to ensuring the continuity of learning. In India, where online education wasn’t traditionally integrated into the primary education system, it is imperative to assess its influence on students. Understanding its effects is crucial for enhancing the quality of online education and gauging its impact on mental health. Our study aimed to evaluate the challenges encountered by senior secondary students in rural schools during the COVID-19 pandemic regarding online education. We examined the prevailing conditions and obstacles faced, while also analyzing the extent to which online education was adopted among them. The study was conducted in year 2022, among 431 senior secondary students. The selection of the students was made through multistage sampling from two blocks of Varanasi i.e. Kashi Vidyapeeth and Chiraigoan. The results show that 39 per cent of students were not much aware of the online classes prior. The majority of students (94.9%) had been using mobile devices to attend classes and for learning purpose. 52.2 per cent expressed concerns about the students’ mental health, and a large majority (95.4%) of students themselves worried about their academic careers.
Keywords: Online learning; Covid-19; Rural students; Senior secondary schools; Challenges